ANALYSIS STUDY OF EMOJI USAGE IN TIKTOK SOCIAL MEDIA - Vilma Dewi Anggraeni; Muchsin al-Fikri; Delvin Musa Navarro Matulessy; Kimmy Azizah Sumengkar (PT Altin Riset Publishing, 2026)
This study aims to analyze the use of emojis in communication on the popular social media platform TikTok among users of various generations. Emojis serve as complements to non-verbal expressions, enhancing emotional conveyance and facilitating message comprehension. Using a qualitative descriptive method and literature study, the research reveals multiple functions of emojis as visual communication tools, cultural symbols, and bridges across language and cultural differences. The findings indicate that emoji use on TikTok not only increases engagement but also reflects generational preferences and meanings, with younger users being more creative and expressive in their emoji usage. This study provides important insights into the role of emojis in effective and meaningful digital communication in the social media era.